2021
DOI: 10.1111/bcpt.13633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dipyrone and acetylsalicylic acid on contractions of distal cauda epididymis duct, serum testosterone and sperm count in rats

Abstract: The effects of dipyrone and acetylsalicylic acid (ASA) on male fertility are still not fully understood, mainly considering the epididymis as a putative target for their anti‐fertility effects. Therefore, this study aimed to investigate the effects of dipyrone and ASA on the contractions of distal cauda epididymis duct, serum testosterone levels and sperm parameters in rats. Firstly, we checked the in vitro effects of dipyrone and ASA (10–1000 μM) on the contractions of distal cauda epididymis duct by pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…In the study of Martins et al . (2021) , conducted on Wistar rats, the effects of aspirin (AAS) and dipyrone on seminal quality were examined.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In the study of Martins et al . (2021) , conducted on Wistar rats, the effects of aspirin (AAS) and dipyrone on seminal quality were examined.…”
Section: Resultsmentioning
confidence: 98%
“…A singular study concerning the adverse effects of dipyrone on male fertility was identified. Martins et al . (2021) adopted a methodology similar to the tests conducted with aspirin (AAS).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations